Epidemiology, Disposition, and Treatment of Ambulatory Veterans With Skin and Soft Tissue Infections. (12th February 2020) - Rhoads, Jamie L W; Willson, Tina M; Sutton, Jesse D; Spivak, Emily S; Samore, Matthew H; Stevens, Vanessa W
Abstract: Background: Most skin and soft tissue infections (SSTIs) are managed in the outpatient setting, but data are lacking on treatment patterns outside the emergency department (ED). Available data suggest that there is poor adherence to SSTI treatment guidelines. Methods: We conducted a retrospective cohort study of Veterans diagnosed with SSTIs in the ED or outpatient clinics from 1 January 2005 through 30 June 2018. The incidence of SSTIs over time was modeled using Poisson regression using robust standard errors. Antibiotic selection and incision and drainage (I&D) were described and compared between ambulatory settings. Anti–methicillin-resistant Staphylococcus aureus (MRSA) antibiotic use was compared to SSTI treatment guidelines. Results: There were 1 740 992 incident SSTIs in 1 156 725 patients during the study period. The incidence of SSTIs significantly decreased from 4.58 per 1000 patient-years in 2005 to 3.27 per 1000 patient-years in 2018 ( P < .001). There were lower rates of β-lactam prescribing (32.5% vs 51.7%) in the ED compared to primary care (PC), and higher rates of anti-MRSA therapy (51.4% vs 35.1%) in the ED compared to PC. The I&D rate in the ED was 8.1% compared to 2.6% in PC. Antibiotic regimens without MRSA activity were prescribed in 24.9% of purulent SSTIs. Anti-MRSA antibiotics were prescribed in 40.1% of nonpurulent SSTIs. Conclusions: We found a decrease in the incidence of SSTIs in the outpatient setting over time. Treatment of SSTIs varied depending on the presenting ambulatory location. There is poor adherence to guidelines in regard to use of anti-MRSA therapies. Further study is needed to understand the impact of guideline nonadherence on patient outcomes. Abstract : Treatment of skin and soft tissue infections (SSTIs) varies depending on the presenting ambulatory location. We found poor adherence to guidelines regarding underuse of anti–methicillin-resistant Staphylococcus aureus therapies for purulent SSTIs and overutilization for nonpurulent SSTIs in the ambulatory setting.